KONSEP AL-TAYSIR DALAM PERBELANJAAN PERKAHWINAN ISLAM: The Concept of al-Taysīr in Islamic Marriage Expenses - Syed Husin, Syh Noorul Madihah; Azahari, Raihanah; Ab Rahman, Asmak (Jurnal Syariah, 2014)
Marriage expenses among Muslims are increasingly more expensive and have a negative impact on their society. They have been burdened by an expense that is not in line with the tenets of Islam, which aim at simplifying the procedures of human life. This article will look into the concept of al-taysīr in wedding expenses, so as to promote marriage in Islam as a simple and uncomplicated process, as long as it complies with Islamic law. This study examines and analyses text and documents related to the jurisprudence of wedding expenses. This article explores the concept of the al-taysīr in wedding expenses. The results show that al-taysīr concept already exists in Islamic wedding expenses. The transparent approach of this concept in Islam encourages couples to manage their wedding expenses based on the ability of the couple and their families to provide a reasonable budget. In addition, Islam also promotes cooperation among Muslims in managing expenses. These findings can be a guide for wedding expenses for couples planning for marriage, in order to ensure spending in the course of marriage to be compliant with Islamic teaching.